Towards a Typology of Social Work Assessments: Developing practice in Malaysia, Nepal, United Kingdom and Vietnam - Jonathan Parker; Sara Ashencaen Crabtree; Azlinda Azman; Bala Raju Nikku; Uyen Thi Tung Nguyen (Social Work and Society, 2018)
This paper offers a cross-cultural, comparative analysis of social work assessments across four countries: Malaysia, Nepal, Vietnam and the UK. Data were gathered from interviews with social work practitioners in each country, from agencies and from policy sources. Social work assessment is understood as a broad but ubiquitous task which concerns the analysis and exploration of social situations, human conditions and needs and acts as a precursor to social work action oriented towards change. Meanings associated with social work assessment are used to introduce an explanatory model by which to offer comparisons and contrasts of some of the ways that social workers analyse social situations and individuals with whom they work. An analysis of perceived priorities and challenges for implementation in respect of assessment as a defining or key professional activity is given in this paper. After considering developments in assessment in the four countries it is argued that there is a gravitational pull towards Westernised assessment models; whereas indigenous exigencies require asserted reflexivity to allow for the development of appropriate synthetic assessment models for each country.